2012
DOI: 10.1080/15283488.2012.716381
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Identity and Romantic Relationship Intimacy Associations with Well-Being in Emerging Adulthood

Abstract: This study examined identity and romantic relationship intimacy associations with emerging adults' well-being. Examination of identity status differences in well-being indicated emerging adults in foreclosed and achieved identity statuses reported higher well-being levels than identity diffuse and moratorium emerging adults. Results also indicated gender moderation of identity status differences in romantic relationship intimacy. Identity diffuse and moratorium women reported more intimate relationships than d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 50 publications
(81 reference statements)
4
15
0
1
Order By: Relevance
“…Results suggested that it is not the financial stress per se that is associated with the difficulties in developing a sense of self inside a significant relationship, but that this variable seems to have an impact on psychological well-being that can interfere with the separationindividuation process. Several studies evidenced the association between dimensions of wellbeing, in general, and self-esteem and depression, in particular, with romantic relationships and intimacy (e.g., Johnson et al, 2012;Joyner and Udry, 2000). In line with identity capital theory (Côté, 2002(Côté, , 2006 and empirical research with Portuguese emerging adults (Oliveira et al, 2014), we propose that self-esteem and absence of depressive mood are psychological resources that are likely to be associated with one's agentic ability to manage the difficulties of the autonomy and individuation process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results suggested that it is not the financial stress per se that is associated with the difficulties in developing a sense of self inside a significant relationship, but that this variable seems to have an impact on psychological well-being that can interfere with the separationindividuation process. Several studies evidenced the association between dimensions of wellbeing, in general, and self-esteem and depression, in particular, with romantic relationships and intimacy (e.g., Johnson et al, 2012;Joyner and Udry, 2000). In line with identity capital theory (Côté, 2002(Côté, , 2006 and empirical research with Portuguese emerging adults (Oliveira et al, 2014), we propose that self-esteem and absence of depressive mood are psychological resources that are likely to be associated with one's agentic ability to manage the difficulties of the autonomy and individuation process.…”
Section: Discussionmentioning
confidence: 99%
“…The associations between quality of romantic relationship and well-being, specially self-esteem and depression, are well documented (Demir, 2008;Galambos et al, 2006;Johnson, Kent and Yale, 2012;Joyner andUdry, 2000, Karney andBradbury, 2005). Research suggests that relationship intimacy and individuation are relevant components in emerging adults' development having a beneficial impact on self-esteem and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, adolescent parasocial romantic relationships may also serve an adaptive purpose, providing adolescents who are just entering the world of dating with the opportunity to explore and decide on romantic and personal identities, to experiment with sexuality, and to seek out desirable traits for future partners without the risk of rejection, reputation loss or negative health outcomes (e.g., STDs or pregnancy; Engle & Kasser, 2005;Karniol, 2001). For those adolescents who successfully utilize parasocial romance as a tool in identity formation, there may be long-term positive outcomes related to relationship satisfaction and personal well-being (Johnson, Kent, & Yale, 2012). As long-term romantic partner selection is a key task of emerging adulthood, adolescents with stronger senses of self and of what they want (possibly due in part to the exploration done through media relationships) may be more successful and satisfied in the pursuit of fulfilling romantic relationships.…”
Section: The Current Studymentioning
confidence: 99%
“…As such, Social Cognitive Theory would suggest that romantic parasocial relationships should enhance media effects at least as much as non-romantic parasocial relationships. Initial research on romantic parasocial attachments suggests that these relationships might heighten media effects on future partner preferences (Adams-Price & Burnett & Beto, 2000), relationship expectancies (Adams-Price & Burnett & Beto, 2000, Segrin & Nabi, 2002, and ultimately, relational happiness and overall well-being (Galliher, Rostosky, Welsh, & Kawaguchi, 1999;Johnson, Kent & Yale, 2012).…”
mentioning
confidence: 98%
“…These relationships provide a means for adolescents to explore and define their romantic and sexual identities (Boon & Lomore, 2001;Engle & Kasser, 2005;Karniol, 2001). Initial evidence suggests that adolescent romantic attachments to media figures could influence a) interpretation of media (Cohen, 2002(Cohen, , 2003, b) development of relational scripts, schemas, and normative beliefs (Basil, 1996;Erickson & Dal Cin, 2017), c) future partner preferences (Adams-Price & Burnett & Beto, 2000), d) relationship expectancies (Adams-Price & Burnett & Beto, 2000, Segrin & Nabi, 2002, and ultimately, e) relational happiness and overall well-being (Erickson & Dal Cin, 2017;Galliher, Rostosky, Welsh, & Kawaguchi, 1999;Johnson, Kent & Yale, 2012).…”
Section: Toward a Multi-dimensional Model Of Adolescent Romantic Paramentioning
confidence: 99%